Continued persistence of non-native ascidians in Southern California harbors and marinas - Claire L. Nichols; Gretchen Lambert; Marie L. Nydam (Aquatic Invasions)
Non-native ascidians have long dominated the artificial structures in southern California’s (United States) marinas and harbors. To determine the change in ascidian abundance and community composition over the last several decades, in 2019–2020 we replicated surveys from 1994–2000. We then created nMDS plots using the abundance data collected in the 1994–2000 and 2019–2020 surveys to compare the two groups. Range and average abundance per species were analyzed to determine trends and changes in ascidian community composition. Of the species used for comparison, four are native, three are cryptogenic, and 12 are non-native. As predicted by Lambert and Lambert, non-native species have persisted in southern California; however, ranges and abundances have changed. The only native species found consistently in both sets of surveys, Ascidia ceratodes, remained rare in 2019–2020, with an unchanged average abundance. Several non-native species increased in abundance or remained common. The non-native colonial species Polyandrocarpa zorritensis had the greatest influence on the dissimilarity between the surveys, increasing from rare in 1994–2000 to more common in 2019–2020, and spreading north to Santa Barbara. Several non-native species confined to San Diego in the 1994–2000 surveys have also spread north, such as Botrylloides giganteus and Styela canopus which were found in Santa Barbara in 2019–2020. A formerly unidentified Aplidium sp. has now been identified as the non-native Aplidium accarense. There have also been additional introductions since 2000, including Ascidia cf. virginea and the first report of Ascidiella aspersa in the NE Pacific. The overwhelming trends of the surveys indicate that we will continue to see an increase and persistence of newly introduced non-natives in Southern California marinas, with possible continued northward expansion.